Strategies for Implementing Bureaucratic Ethics in Providing Business Permit Services at the Makassar City Integrated Licensing and Investment Board Office (BPTPM) - Pananrangi, Andi Rasyid; Nurkaidah, Nurkaidah (Journal of Asian Multicultural Research for Social Sciences Study, 2021)
This study aims to analyze the Strategy of Applying Bureaucratic Ethics in Providing Business License Services at the Makassar City BPTPM Office. This research method uses a qualitative research approach. Primary data were obtained by researchers through in-depth interviews with informants, observations in the object of research, and document searches at the Makassar City BPTPM. The results showed that the strategy of implementing bureaucratic ethics in the provision of business license services in Makassar City with the results showing that the registration of business licenses with the online system was considered adequate and in terms of quality it was concluded that it was inadequate for the licensing service process. which is programmed by the government with what the community expects, and on time services in business license services, no apparatus shows adequate achievements. The strategy for implementing BPTPM bureaucratic ethics is expected to be able to respond quickly to people who need licensing management services.